Productivity and Profitability of Cassava under Drip Fertigation - Sunitha, S; George, James; Sureshkumar, J (JOURNAL OF ROOT CROPS, 2017)
Productivity and profitability of cassava under drip fertigation and rain fed cultivation was worked out, based on the data collected from field experiments carried out at ICAR-CTCRI, Thiruvananthapuram, during the period 2014-15, 2015-16 and 2016-17. The trial was conducted by planting mini setts of short duration variety cassava, â€œSree Vijayaâ€ with three levels each of nitrogen and potassium in factorial design along with a control (rainfed crop with soil application of fertilizers). The tuber yield was 2 to 3 times higher under drip fertigation compared to rainfed crop. The mean data over a period of three years indicated that drip fertigation @ 75 kg nitrogen and 125 kg potash resulted in maximum tuber yield, gross and net income and B:C ratio in cassava. Drip fertigation is profitable in cassava, especially in the industrial belts, and N and K @ 75: 125 kg ha-1 could result in 4.4 times increase in net income and 67% increase in B:C ratio.